Influence of tin oxide decoration on the junction conductivity of silver nanowires. (23rd April 2023) - Vogl, Lilian Maria; Kalancha, Violetta; Schweizer, Peter; Denninger, Peter; Wu, Mingjian; Brabec, Christoph; Forberich, Karen; Spiecker, Erdmann
Abstract: Flexible electrodes using nanowires (NWs) suffer from challenges of long-term stability and high junction resistance which limit their fields of applications. Welding via thermal annealing is a common strategy to enhance the conductivity of percolated NW networks, however, it affects the structural and mechanical integrity of the NWs. In this study we show that the decoration of NWs with an ultrathin metal oxide is a potential alternative procedure which not only enhances the thermal and chemical stability but, moreover, provides a totally different mechanism to reduce the junction resistance upon heat treatment. Here, we analyze the effect of SnO x decoration on the conductance of silver NWs and NW junctions by using a four-probe measurement setup inside a scanning electron microscope. Dedicated transmission electron microscopy analysis in plan-view and cross-section geometry are carried out to characterize the nanowires and the microstructure of the junctions. Upon heat treatment the junction resistance of both plain silver NWs and SnO x -decorated NWs is reduced by around 80%. While plain silver NWs show characteristic junction welding during annealing, the SnO x -decoration reduces junction resistance by a solder-like process which does not affect the mechanical integrity of the NW junction and is therefore expected to be superior for applications.